EVALUATION OF SUPPLEMENTAL PHOTODYNAMIC THERAPY FOR POSTOPERATIVE PAIN IN ENDODONTICS - Misbah Ashfaq; Ghafeer Ahmad Malik; Saroosh Ehsan; Talha Ahmad Malik; Adeela Rafique; Ayesha Nadeem (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Photodynamic therapy (PDT) is an emerging adjunct in endodontic treatment, aimed at reducing postoperative pain. Conventional root canal disinfection methods may not always achieve complete microbial elimination, necessitating the exploration of alternative approaches like PDT. Objective: This study aimed to evaluate the effectiveness of photodynamic therapy (PDT) as an adjunct in endodontic treatment by assessing its impact on postoperative pain and associated symptoms compared to conventional methods. Methods: A quasi-experimental study was conducted on 50 patients (25 per group) requiring root canal treatment for apical periodontitis. The experimental group (PDT) received photodynamic therapy using toluidine blue and a red laser (30 mW, 9 J/cm² for 90 seconds), while the control group (CMP) underwent conventional disinfection. Postoperative pain was measured using a visual analog scale (VAS) at 24, 48, and 72 hours. Results: The mean age of participants was 35.6 ± 8.4 years in the experimental group and 36.2 ± 7.9 years in the control group. The majority of participants were male, comprising 68.0% (n=17) in the experimental group and 64.0% (n=16) in the control group, while females accounted for 32.0% (n=8) and 36.0% (n=9), respectively. The mean radiolucency size was 3.5 ± 1.1 mm in the experimental group and 3.4 ± 1.0 mm in the control group. The mean postoperative pain score (VAS) at 24 hours was significantly lower in the experimental group (PDT) (2.8 ± 1.1) compared to the control group (CMP) (4.5 ± 1.4) (p = 0.001), indicating that PDT was effective in reducing postoperative pain. Conclusion: Photodynamic therapy (PDT) effectively reduces early postoperative pain in endodontic treatment, with significant pain relief observed within the first 72 hours. However, its long-term benefits remain uncertain as pain levels between groups equalize after one week.